JAK1-dependent transphosphorylation of JAK2 limits the antifibrotic effects of selective JAK2 inhibitors on long-term treatment. Issue 8 (6th May 2017) - Zhang, Yun; Liang, Ruifang; Chen, Chih-Wei; Mallano, Tatjana; Dees, Clara; Distler, Alfiya; Reich, Adam; Bergmann, Christina; Ramming, Andreas; Gelse, Kolja; Mielenz, Dirk; Distler, Oliver; et al.
Abstract : Objectives: Janus kinase 2 (JAK2) has recently been described as a novel downstream mediator of the pro-fibrotic effects of transforming growth factor-β. Although JAK2 inhibitors are in clinical use for myelodysplastic syndromes, patients often rapidly develop resistance. Tumour cells can escape the therapeutic effects of selective JAK2 inhibitors by mutation-independent transactivation of JAK2 by JAK1. Here, we used selective JAK2 inhibition as a model to test the hypothesis that chronic treatment may provoke resistance by facilitating non-physiological signalling pathways in fibroblasts. Methods: The antifibrotic effects of long-term treatment with selective JAK2 inhibitors and reactivation of JAK2 signalling by JAK1-dependent transphosphorylation was analysed in cultured fibroblasts and experimental dermal and pulmonary fibrosis. Combined JAK1/JAK2 inhibition and co-treatment with an HSP90 inhibitor were evaluated as strategies to overcome resistance. Results: The antifibrotic effects of selective JAK2 inhibitors on fibroblasts decreased with prolonged treatment as JAK2 signalling was reactivated by JAK1-dependent transphosphorylation of JAK2. This reactivation could be prevented by HSP90 inhibition, which destabilised JAK2 protein, or with combined JAK1/JAK2 inhibitors. Treatment with combined JAK1/JAK2 inhibitors or with JAK2 inhibitors in combination with HSP90 inhibitors was more effective than monotherapy with JAK2 inhibitors in bleomycin-induced pulmonary fibrosis and in adTBR-induced dermal fibrosis. Conclusion: Fibroblasts can develop resistance to chronic treatment with JAK2 inhibitors by induction of non-physiological JAK1-dependent transactivation of JAK2 and that inhibition of this compensatory signalling pathway, for example, by co-inhibition of JAK1 or HSP90 is important to maintain the antifibrotic effects of JAK2 inhibition with long-term treatment.